Factors affecting left ventricular remodeling after valve replacement for aortic stenosis. An overview - Villa, Emmanuel; Troise, Giovanni; Cirillo, Marco; Brunelli, Federico; Tomba, Margherita Dalla; Mhagna, Zen; Tasca, Giordano; Quaini, Eugenio (Cardiovascular ultrasound, 2006)
Although a small percentage of patients with critical aortic stenosis do not develop left ventricle hypertrophy, increased ventricular mass is widely observed in conditions of increased afterload. There is growing epidemiological evidence that hypertrophy is associated with excess cardiac mortality and morbidity not only in patients with arterial hypertension, but also in those undergoing aortic valve replacement. Valve replacement surgery relieves the aortic obstruction and prolongs the life of many patients, but favorable or adverse left ventricular remodeling is affected by a large number of factors whose specific roles are still a subject of debate. Age, gender, hemodynamic factors, prosthetic valve types, myocyte alterations, interstitial structures, blood pressure control and ethnicity can all influence the process of left ventricle mass regression, and myocardial metabolism and coronary artery circulation are also involved in the changes occurring after aortic valve replacement. The aim of this overview is to analyze these factors in the light of our experience, elucidate the important question of prosthesis-patient mismatch by considering the method of effective orifice area, and discuss surgical timings and techniques that can improve the management of patients with aortic valve stenosis and maximize the probability of mass regression.